The Effect of Compensation and Performance Appraisal on Employee Performance through Employee Engagement at PT. Agincourt Resources - Lilly Linne Kainde; Lingkan Pagala (PT FORMOSA CENDEKIA GLOBAL, 2022)
The main objective of this study is to analyze and determine the effect of compensation and performance appraisal on employee performance with employee engagement as an intervening variable. Sampling using non-probability sampling with purposive sampling technique with the number of respondents used amounted to 127 people. The type of research used is descriptive and structural/pathological research with data analysis. The results obtained include: 1) Compensation has a significant effect on employee engagement; 2) Performance appraisal has a significant effect on employee engagement; 3) Employee engagement has no effect on employee performance; 4) Compensation has a significant effect on employee performance; 5) Performance appraisal has no effect on employee performance